PRMT3 interacts with ALDH1A1 and regulates gene-expression by inhibiting retinoic acid signaling - Mamta Verma (Nature Portfolio, 2021)
Here, the authors demonstrate that protein arginine methyltransferase 3 (PRMT3) interacts with and inhibits the retinal dehydrogenase ALDH1A1, negatively regulating the expression of retinoic acid responsive genes. This study shows that PRMT3 affects diverse biological processes not only by globally regulating protein function through methylation but also by regulating gene expression.